PROTOTYPE SISTEM MONITORING KETINGGIAN AIR DAN CURAH HUJAN DI BENDUNGAN CIKALUMPANG BERBASIS INTERNET OF THINGS (IOT) - Ramdani Budiman; Tifani Intan Solihati; Khasan Asrori; Iman Faturohman; Raden Kania (Jurnal Sistem Informasi dan Informatika (Simika), 2026)
Cikalumpang Dam, located in Kadubeureum Village, Padarincang District, Serang, Banten Province, is an irrigation area under the authority of Banten Province and managed by the Ciujung-Cidanau Watershed Management Unit UPTD (PDAS). Rising water levels in the dam, influenced by heavy rainfall and high river discharge, have become a recurring issue. Currently, water level measurement is conducted manually using conventional tools, causing delays in delivering crucial information to officers. Such delays increase the risk of flooding, which can damage infrastructure, harm the environment, and threaten human safety. The 2023 flood in Citasuk Village illustrates the risks caused by inadequate monitoring systems. This research applies a prototype method to develop an Internet of Things (IoT)- based water level and rainfall monitoring system integrated with the Blynk application. The system employs an ultrasonic sensor to measure water levels and a rainfall sensor to monitor precipitation in real-time, with data sent directly to the Blynk platform for monitoring and notification. The development stages include requirement analysis, prototype construction, system evaluation, coding, and testing. The system is designed to provide rapid alerts, enabling timely intervention to reduce flood risks. The main objective of this research is to improve water resource management efficiency at Cikalumpang Dam through modern technology implementation. Accurate and responsive monitoring is expected to minimize the negative impacts of flooding and enhance public safety. This study contributes to the development of intelligent solutions for water resource management and disaster mitigation.